The Effectiveness of the Pteridophyta Diversity E-Module in the Sikarim Waterfall Area as a Biology Teaching Material on the Cognitive Learning Outcomes of Grade X Students - Kastimah, Umi Latifah; Ericka, Ericka Darmawan; Serafica Btari Christiyani Kusumaningrum (Bioeduca : Journal of Biology Education, 2024)
The objectives of this research are as follows: 1) find out what types of ferns (Pteridophyta) exist in the SikarimWaterfall area. 2) Knowing the suitability of e-modules as biology teaching materials for students. 3) Analyze the effectiveness of e-modules on students' cognitive learning outcomes. The research method used is the Research and Development (R&D) 4D model. At the dissemination stage, a small-scale trial was carried out with a one-group pretest post-test design. The subjects in this research were class X-7 students at SMAN 1 Mojotengah. The results of this research show that the e-module based on the potential of Pteridophyta in the Sikarim Waterfall Area is suitable for use as teaching material on biodiversity material, with scores obtained from material experts of 93.22% and media experts of 87.17% as well as filling in responses from participants students amounted to 82.22% and teacher responses amounted to 95.57%. The effectiveness of e-modules on student learning outcomes is based on the N-Gain value. The calculation results show differences in the pretest and post-test results. The increase in student learning outcomes is categorized as high, with an N-Gain of 0.789. Therefore, it can be concluded that the e-module based on the potential of Pteridophyta in the Sikarim Waterfall Area is feasible and effective for use as biology teaching material on biodiversity